ACCESSION OF THE REPUBLIC OF MOLDOVA TO THE EUROPEAN UNION WITH OR WITHOUT A DEFINED STATUS OF THE TRANSNISTRIAN REGION - Cara, Eugen (CEP USM, 2024)
This scientific article aims to analyze the perspective of the European integration of the Republic of Moldova in the context of the unresolved Transnistrian conflict, a controversial public topic, starting with the establishment of its first relations with the European Union until today, when Chisinau began accession negotiations. Some voices strongly believe that Moldova’s accession to the European Union is conditional on the final and sustainable settlement of the Transnistrian conflict, because neither the territorial conflict nor the Russian army, which has been illegally stationed in the country for over three decades, can be imported into the European Union, or, the accession without the Transnistrian region could mean Chisinau ceding a part of the state territory, where about 360 thousand of its citizens live. A part of society, on the contrary, claims that the European Union has never conditioned its expansion by a priori solving the territorial problems faced by the candidate countries, and the Transnistrian conflict is a lever of Moscow’s influence to block the European path of the Republic of Moldova. The analysis, in essence, of the problem of the European integration of the Republic of Moldova in the context of the Transnistrian conflict allowed the formulation of some conclusions that could contribute positively to the achievement of the country’s European accession goal.
ADERAREA REPUBLICII MOLDOVA LA UNIUNEA EUROPEANĂ CU SAU FĂRĂ STATUT DEFINIT AL REGIUNII TRANSNISTREI
Keywords: conflict; European integration; territorial reiteration; security; integrare europeană; reintegrare teritorială; securitate